Can Equivalency Programs (EPs) Align Formal Education Standards? Evaluating Teacher Proficiency of Emancipated Curriculum Implementation in West Java Province - Anggrayni, Yenni (Pusbindiklatren Bappenas, 2025)
Teacher performance is a critical factor in accreditation assessments for Equivalency Programs (EPs) in Indonesia. In 2023, 62.05% of EPs in West Java remained unaccredited due to failure to meet national education standards.. To address this issue, the Indonesian government introduced the Merdeka Belajar (Emancipated Curriculum) in 2022, aiming to standardize learning processes between formal schools and EPs. This study evaluates teachers’ proficiency in implementing the curriculum across 83 EPs in West Java, based on an online survey of 282 teachers selected by accreditation level. Quantitative analysis using generalized ordinal logistic regression (gologit2) revealed that teacher proficiency was categorized as